THE METHODS OF ACQUIRING LEGAL PERSONALITY OF INTERNATIONAL ORGANIZATIONS - Hoca, Elif (International Scientific Journal Vision, 2023)
International legal personality, in terms of units, can be characterized as an indicator of presence in the international arena. Accordingly, the ways of acquiring the legal personality of international organizations in the international arena are subject to distinction. These methods are considered as a continuation of the abovementioned theories and are listed as follows; It is divided into four parts: acquiring by treaty, implicit (implicit) acquiring, personality given by central treaties, and finally, personality gained by the decision of the United Nations General Assembly. It has been stated that international organizations have the personality of international law as well as various rights and obligations. However, although every international organization can’t have this international legal personality, it has been established in a system in the form of certain criteria